Response of Sweet Corn Plants (Zea mays saccharata L.) Affected the Aplication of Biological Liquid Compound Fertilizer and Synthetic Fertilizer N, P and K - Arifah Rahayu; Nur Rochman; Nurfitri Dwi Lestari; Karlin Agustina (JURNAL AGRONIDA, 2018)
This study was aimed at assessing the response of sweetcorn plant on various dosages ofbiofertilizer and synthetic (N, P and K) fertilizer. The study was done in May to September 2014 atthe Agrotechnology Trial Farm of Djuanda University. A factorial completely randomized designwas used. The first and second factor were biofertilizer and synthetic fertilizer dosage (0%, 50 %,100% and 150% R/Recommendation). Results showed that adding biofertilizer and syntheticfertilizer until 100% R increased leaf area, length and weight of ear, root and biomass weight andTSS (total soluble solids) content. At various level of biofertilizer, increasing synthetic fertilizerdosages until 100% R could improve plant height, leaves and root number, stem girth, ear lengthand accelerate growing of staminate and pistillate. Meanwhile at various degree of syntheticfertilizer dosage, raising bofertilizer dosage until 150% R tend to higher plant height, and until100% R caused stem girth and root length greater, but delayed staminate and pistillate growth.Application of biofertlizer and synthetic fertilizer tend to increasing pH and cation exchangecapacity of growth medium.Keywords: weight of ear, pH, cation enxchange capacity